Sistem Pemberi Makan dan Minum Pintar Pada Hewan Peliharaan Berbasis Website dan Aplikasi Android - Setiawan, Kevin; Lukas, Lukas; Panjaitan, MM Lanny (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2023)
Based on a survey by “Mars”, about 59% of dogs and 52% of cats weighed more than they should. This is the motivation of this research in designing a feeding and drinking automation for pets so that it is easier for owners to take care their pet's health diet, and so that owners don't have to worry about forgetting to feed their pets. To connect to the internet, ESP32 is used. The supporting components consist of load cell (weight sensor), three ultrasonic sensors (proximity sensor), servo motor and pump motor. These components are combined to carry out the function of feeding and drinking automatically. The device will run after being given an order via website or application. For the feeding system, the animal owner can provide input on the schedule, frequency and portion of feeding. While the drinking system, the owner can press the calibration button and the pause button. Tests are carried out on each sensor, to measure its accuracy and testing of the entire system is carried out to ensure all components work together to carry out their functions. The test results show that every hardware and software component has worked in accordance with the designed objectives.